A Handbook of Transcription Factors - Hughes, Timothy R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Transcription factors are - in the most common use of the term - proteins that possess sequence-specific DNA-binding activity, and either directly or indirectly influence the transcription of genes in proximity to the binding site. Transcription factors are the primary interface between the cell and the genome, and in aggregate control not only regulation of transcription but also genome organization, and play a central role in many aspects of physiology and evolution. This book will provide a reference for the major aspects of transcription factor biochemistry, function, and evolution. Contents will range from a general catalogue of known transcription factor classes, origins and evolution of transcription factor types, and mechanisms of interaction with chromatin, the nuclear scaffold, and RNA polymerase.
Preface -- 1 Introduction to A Handbook of Transcription Factors, Timothy R. Hughes -- 2 An Index of Prokaryotic Transcription Factors, Karthikeyan Sivaraman et al. -- 3 A Catalogue of Eukaryotic Transcription Factor Types, their Evolutionary Origin, and Species Distribution, Matthew T. Weirauch and Timothy R. Hughes -- 4 Function and Evolution of C2H2 Zinc Finger Arrays, Lisa Stubbs, Younguk Sun and Derek Caetano-Anolles -- 5 Homeodomain Sybtypes and Functional Diversity, Thomas R. Bürglin -- 6 Nuclar Receptors, Keith Pardee, Aleksander S. Necakov, Henry Krause -- 7 Methods for Analysis of Transcription Factor DNA-binding Specificity in vitro, Arttu Jolma, Jussi Taipale -- 8 Identification of Transcription Factor-DNA Interactions in vivo, Duncan T. Odom -- 9 How Transcription Factors Identify Regulatory Sites in Genomic Sequence, Yair Field, Eilon Sharon, Eran Selgal -- 10 Transcription Factor in Binding Sites and other Features in Human and Drosophila Proximal Promoters, Charles Vinson, Raghunath Chatterjee, Peter Fitzgerald -- 11 Interactions of Transcription Factors with Chromatin, Harm van Bakel -- 12 Transcription Factors Effector Domains, Seth Frietze, Peggy J. Farnham -- 13 Large-scale Nuclear Architecture and Transcriptional Control, Juan M. Vaquerizas, Asifa Akhtar, Nicholas M. Luscombe -- Index.
Keywords: Medicine; Biochemistry; Nucleic acids; Cytology; Biomedicine; Biomedicine general; Biochemistry, general; Nucleic Acid Chemistry; Cell Biology